2008
DOI: 10.3233/ch-2008-1072
|View full text |Cite
|
Sign up to set email alerts
|

Impaired erythrocytes deformability in H2O2-induced oxidative stress: Protective effect of L-carnosine

Abstract: Impaired red blood cell deformability is a hemorheological perturbation induced by many kinds of diseases. An increase in free radicals causes a reduction in erythrocyte flexibility and deformability. Carnosine is a dipeptide abundant in skeletal muscle and brain of humans. One of the main function of carnosine is its antioxidant and free-radical scavenger effect. In this study our aim is to investigate the protective effect of L-carnosine on RBCs in H 2 O 2 -induced oxidative stress in vitro conditions.Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The elevation in the kidney biomarkers was due to the direct toxic effect of CP on the glomerular and tubular structures through the generation of ROS. Contraction of the mesangial cells with subsequent alteration in the filtration surface area resulted from the generation of ROS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevation in the kidney biomarkers was due to the direct toxic effect of CP on the glomerular and tubular structures through the generation of ROS. Contraction of the mesangial cells with subsequent alteration in the filtration surface area resulted from the generation of ROS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The escalation in the serum levels of these renal functional markers might be caused by the direct toxic effect of CDDP that resulted in: impaired renal functions (Anusuya et al, 2013), glomerular injury, tubular obstruction and/or the back-leakage of the renal tubules (Azu et al, 2010). The alterations in glomerular function in CDDP-treated rats may also be secondary to ROS (Somani et al, 2000) which provoke mesangial cells contraction, modifying the filtration surface area and altering the ultrafiltration coefficient factors that decrease the glomerular filtration rate (Aydogan et al, 2008). Such ROS might play a role in the pathogenesis of tubular cell apoptosis but probably had no effect in the tubular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the observed nephrotoxicity due to cisplatin treatment was manifested by marked increases in serum creatinine, urea and uric acid accompanied by a decrease in urine creatinine, urea, uric acid and creatinine clearance. This may be due to the decrease in the glomerular filtration rate or may be secondary due to the increase of the reactive oxygen species (Noori and Mahboob 2010) which induce mesangial cells contraction, altering the filteration surface area and modifying the ultrafiltration coefficient factors that thereby decrease the glomerular filtration rate (Aydogan et al 2008). These results are in accordance with previous studies (Fouad et al 2008).…”
Section: Discussionmentioning
confidence: 99%